2009
DOI: 10.1093/mutage/gep029
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 75 marketed pharmaceuticals using the GADD45a-GFP ‘GreenScreen HC’ genotoxicity assay

Abstract: The GADD45a-GFP (GreenScreen HC) reporter assay detects genotoxic damage in the human lymphoblastoid TK6 cell line and gives positive results for all classes of genotoxin, including mutagens, aneugens and clastogens. In this study, a collection of 75 marketed pharmaceuticals were tested in the assay. Compounds in the collection represent a broad range of chemical structures, pharmacologies and therapeutic indications, including neoplasia and viral infection where positive genotoxicity results are often associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 20 publications
5
38
1
Order By: Relevance
“…group. The results of our work agree with the previously reported micronucleus induction by the anthracycline antibiotic epirubicin in murine cancer cells in vitro (Jeremic et al, 1996), in the erythrocytes of incubated hen's eggs (Wolf et al, 2008), and in the human lymphoblastoid TK6 cell line (Hastwell et al, 2009). In addition, the anthracycline antibiotic doxorubicin has been reported to induce micronuclei, chromatid and chromosome breaks, and numerical chromosome aberrations in vivo and in vitro (Schmid, 1976;Maier and Schmid, 1976;Nersessian et al, 1991;Jeremic et al, 1996;Dhawan et al, 2003;Venkatesh et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…group. The results of our work agree with the previously reported micronucleus induction by the anthracycline antibiotic epirubicin in murine cancer cells in vitro (Jeremic et al, 1996), in the erythrocytes of incubated hen's eggs (Wolf et al, 2008), and in the human lymphoblastoid TK6 cell line (Hastwell et al, 2009). In addition, the anthracycline antibiotic doxorubicin has been reported to induce micronuclei, chromatid and chromosome breaks, and numerical chromosome aberrations in vivo and in vitro (Schmid, 1976;Maier and Schmid, 1976;Nersessian et al, 1991;Jeremic et al, 1996;Dhawan et al, 2003;Venkatesh et al, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that epirubicin induces micronuclei in SCCVII murine carcinoma cells (Jeremic et al, 1996), in the erythrocytes of incubated hen's eggs (Wolf et al, 2008), and in the human lymphoblastoid TK6 cell line (Hastwell et al, 2009), structural chromosome aberrations in cultured HeLa cells (Cantoni et al, 1989), both structural and numerical chromosomal aberrations (CA) and sister chromatid exchanges (SCEs) in Chinese hamster cell line (Othman, 2000), and chromosomal aberrations and SCEs in peri pheral blood lymphocyte cultures from women with breast cancer treated by epirubicin-containing regimen in vitro (Silva et al, 2002), genotoxic effects in Drosophila melanogaster (Lehmann et al, 2003), and clastogenic effects in rat bone marrow cells in vivo (Nersessian et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Authors have observed that clomiphene showed a dose-dependent increase in genomic instability and micronucleus frequency in bone marrow stem cells of rats (Duran et al 2006). Hastwell et al (2009) reported that clomiphene has no genotoxic affect on the human lymphoblastoid TK6 cell line using the GADD45a-GFP ''Green Screen HC'' genotoxicity assay. Yılmaz et al (2014) reported that 0.4, 0.8, 1.6 and 3.2 lg/mL concentrations of clomiphene caused significant increase in chromosomal aberrations, micronucleus frequency and DNA damage (comet assay) in human lymphocytes.…”
Section: Genotoxicitymentioning
confidence: 99%
“…The choice of the pathways was mostly based on microarray experiments with genotoxic substances. The GreenScreen HC assay, which uses p53-competent TK6 lymphoblastoid cell line genetically modified to incorporate a fusion cassette containing the GADD45alfa promoter (and other regulatory elements) and the GFP gene as reporter (Hastwell et al, 2006), has been widely characterised and its good sensitivity and specificity confirmed in independent studies (Hastwell et al, 2009;Jagger et al, 2009;Birrel et al, 2010). HTS luciferase reporter assays based on four different stress pathways (RAD51C, Cystatin A, p53 and Nrf2) in the HepG2 cell line have also been developed and shown to be useful for pre-screening in early phases of drug development (Westerink et al, 2010).…”
Section: Genotoxicity Assays Based On Induction Of Dna Damage Responsmentioning
confidence: 99%